Gender Budgeting: A Useful Approach for Aotearoa New Zealand - Suzy Morrissey (New Zealand Government, The Treasury, 2018)
Gender budgeting provides a way of analysing government expenditure and fiscal policy to promote gender equality. It can take many forms in practice including analysis of budget allocations, the structure of fiscal policies, expenditure tracking and monitoring systems to identify gender bias, whether explicit or implicit. It is generally understood that to ensure success such initiatives should be supported by both government and civil society. The concept of gender budgeting is now accepted globally, gaining the support of the OECD, the United Nations, the ILO, and the IMF. Some form of gender budgeting is now undertaken in over 80 countries, and while there have historically been many examples of effective application in developing countries, it is now also gaining popularity in OECD and G7 countries as they seek to address gender equality issues. This paper includes an example of gender analysis on tax concessions but other studies have focused on health, education, and labour market incentives. New Zealand has not introduced any formal gender budgeting initiatives. In this paper, its 2016 Tax Expenditure Statement was reviewed, and identified as lacking any gender specific analysis but including a number of expenditures that could have a potentially negative impact on gender equality. Tax expenditures are generally not recognised and treated as expenditure, although the financial impact is the same, and this small example illustrates how gender budgeting has the potential to provide greater transparency and analysis of expenditure on tax concessions. The paper discusses increasing the transparency of tax expenditures as an example of how gender budgeting could increase fiscal transparency in New Zealand. This paper argues that New Zealand would benefit from exploring the potential application of gender budgeting principles to increase the transparency of fiscal policy and inform policy debate.
Keywords: H2; H5; I3; J16; J18; 330; Gender budgeting; gender analysis; tax expenditure